Pengaruh Kepemimpinan Yang Dinamis Dalam Memajukan Organisasi Muhammadiyah Di Kabupaten Luwu - Sri lestari; Samsul Bachri; Sari Ratna Dewi (Pusat Riset dan Inovasi Nasional, 2025)
Leadership is able to influence employees to work with maximum quantity and quality of work to achieve organizational goals. Etymologically, Muhammadiyah comes from Arabic, from the Kata